Bone marrow transplantation for chronic myeloid leukemia: the use of histocompatible unrelated volunteer donors. - Mackinnon, S; Hows, J; Goldman, J; Arthur, C; Hughes, T; Apperley, J; Jones, L; Batchelor, JR; Brookes, P; Catovsky, D (1990)
We treated 17 patients with chronic myeloid leukemia (CML) by bone marrow transplantation using marrow from human leukocyte antigen (HLA)-matched unrelated donors. Patients were conditioned with a combination of in vivo monoclonal antibodies, chemotherapy with daunorubicin (n = 7) or busulfan (n = 10) and cyclophosphamide, and both total body and total lymphoid irradiation. Donor marrow was depleted of T cells by incubation with monoclonal antibodies of the Campath series. Fourteen (88%) of 16 evaluable patients had sustained engraftment. Four (27%) of the 15 evaluable patients developed acute graft-versus-host disease (GVHD) of grade II or greater, and 4 of 12 evaluable patients developed chronic GVHD. Three patients developed hematological and two developed cytogenetic evidence of relapse. Eight patients (47%) survive at a median follow-up of 32 months (range 10-51 months), giving an actuarial survival of 44%. Five patients remain alive without evidence of hematological or cytogenetic relapse, giving an actuarial disease-free survival of 27%. Pneumonitis caused or contributed to death in six of the nine patients who died. We conclude that T-cell depletion can prevent the severest forms of GVHD but also increases the risk of relapse after transplant with unrelated donors, as it does with HLA-identical siblings. Nevertheless the use of matched unrelated donors should be considered for CML patients who lack HLA-identical siblings.